THE DICTIONARY OF MODERN PROVERBS: SECOND SUPPLEMENT - Clay Doyle, Charles; Mieder, Wolfgang (Proverbium - Yearbook, 2018)
This is the second supplement to The Dictionary of Modern Proverbs (New Haven, Connecticut: Yale University Press, 2012) edit-ed by Charles Clay Doyle, Wolfgang Mieder, and Fred R. Shapiro. It registers 57 additional modern Anglo-American proverbs with historical dates and contextualized references. We intend to publish such supplements from time to time, and eventually hope to bring out a new edition of our dictionary.